Penggunaan Media Gambar dalam Proses Pembelajaran Siswa Kelas IV Sekolah Dasar - Adila Ramadani; Rara Khairani Arfi; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this research is to understand how visual media is used in fourth-grade elementary education, and how visual media affects students' engagement and understanding of learning activities. This research is important as it highlights the benefits of visual learning to enhance knowledge transmission, especially in elementary schools. Data for this descriptive qualitative research was collected through documentation, interviews, and observations. The results show that teachers and fourth-grade students at one elementary school in Padang can help students remember, become more focused, and understand more complex concepts. According to the teacher, the use of visual media makes lessons more engaging and interactive. Thus, visual media is a useful teaching strategy to enhance learning in fourth-grade elementary classrooms. Teachers are encouraged to use more creativity and variety when selecting and creating visual materials that are appropriate for the curriculum and the needs of the students.